Population structure and distribution of Abies spectabilis (D. Don) in Central Nepal Himalaya: A comparison with the total woody vegetation of the forests at the three different elevation ranges in Manang District - Kharal, D. K.; Bhuju, D. R.; Gaire, N. P.; Rayamajhi, S.; Meilby, H.; Chaudhary, A. (Banko Janakari, 2015)
Population structure and distribution of vegetation are often affected by elevation induced climate variation in the Himalaya. This research aims at assessing the population structure and distribution of Abies spectabilis in three different elevation sites within the forests areas in Manang District of central Nepal. Vegetation sampling was conducted during Sept-Oct 2012 and the population information of all the woody vegetation from a total of 59 concentric circular sampling plots of 10 m radii along the transect line were collected. The middle elevation site was characterized by the highest density of seedlings (15,044/ha), saplings (1,629/ha), poles (272/ha) and trees (179/ha) of all woody vegetation. In this elevation, the highest proportion was contributed by A. spectabilis (54%) at combined-level in spite of the lack of large-sized stems (dbh > 70 cm). The proportion of A. spectabilis stem was nearly one-fourth of all the woody vegetation while its lowest proportion (15.5%) was found at the lower elevation at combined-level. On the contrary, its basal area proportion was nearly the half of all the woody vegetation at the lower elevation site, nearly one-third at the middle elevation site and less than 10% at the upper elevation site. There was a significant variation in mean density and basal areas of all stem categories among the sampled sites except the seedling density of all the woody vegetation between the lower and the middle elevations. The stem distribution of all the woody vegetation including A. spectabilis demonstrated the characteristics of normal (sustainable) forest in Manang District. The presence of only small-sized trees with good recent regeneration of A. spectabilis in the upper treeline ecotone revealed stand densification as well as its potential for upward migration in response to environmental change including climate change in future. Banko Janakari; A Journal of Forestry Information for Nepal Vol. 25, No. 1 Page: 3-14